PRECISE Photonic Hybrid Electromagnetic Solver - Davide Bazzanella; Mattia Mancinelli; Massimo Borghi; Paolo Bettotti; Lorenzo Pavesi (IEEE Photonics Journal, 2022)
PRECISE, Photonic hybRid EleCtromagnetIc SolvEr, is a Matlab-based library to model large and complex photonic integrated circuits. Each circuit is modularly described in terms of waveguide segments connected through multi-port nodes. Linear, nonlinear, and dynamical phenomena are simulated by solving the system of differential equations describing the effect to be considered. By exploiting the steady-state approximation of the electromagnetic field within each node device, the library can handle large and complex circuits even on desktop PCs. We show that the steady-state assumption is fulfilled in a broad number of applications and we compare its accuracy with an analytical model (coupled mode theory) and experimental results. PRECISE is highly modular and easily extensible to handle equations different from those already implemented and is, thus, a flexible tool to model the increasingly complex photonic circuits.